2019
DOI: 10.1126/sciadv.aav4416
|View full text |Cite
|
Sign up to set email alerts
|

A neuronal molecular switch through cell-cell contact that regulates quiescent neural stem cells

Abstract: The quiescence of radial neural stem cells (rNSCs) in adult brain is regulated by environmental stimuli. However, little is known about how the neurogenic niche couples the external signal to regulate activation and transition of quiescent rNSCs. Here, we reveal that long-term excitation of hippocampal dentate granule cells (GCs) upon voluntary running leads to activation of adult rNSCs in the subgranular zone and thereby generation of newborn neurons. Unexpectedly, the role of these excited GC neurons in NSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 55 publications
1
45
0
1
Order By: Relevance
“…Additionally, in AD conditions, mammalian NSCs reduce the proliferative ability dramatically, and for neurogenesis to become a viable option for treatment of neurological disorders, mammalian NSCs must become plastic first. Therefore, examining how NSCs could be made proliferative and neurogenic during the course of AD could provide important clinical ramifications towards the treatment of this disease (Kizil and Bhattarai, 2018a); however, little is known about the mechanisms by which neural stem cells would enhance their proliferative response (Dong et al, 2019;Kempermann et al, 2018;Morrens et al, 2012). Recently, we established a zebrafish model, which can recapitulate the symptoms of AD in humans such as neuronal death, synaptic degeneration, chronic inflammation and cognitive decline (Bhattarai et al, 2017a;Bhattarai et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in AD conditions, mammalian NSCs reduce the proliferative ability dramatically, and for neurogenesis to become a viable option for treatment of neurological disorders, mammalian NSCs must become plastic first. Therefore, examining how NSCs could be made proliferative and neurogenic during the course of AD could provide important clinical ramifications towards the treatment of this disease (Kizil and Bhattarai, 2018a); however, little is known about the mechanisms by which neural stem cells would enhance their proliferative response (Dong et al, 2019;Kempermann et al, 2018;Morrens et al, 2012). Recently, we established a zebrafish model, which can recapitulate the symptoms of AD in humans such as neuronal death, synaptic degeneration, chronic inflammation and cognitive decline (Bhattarai et al, 2017a;Bhattarai et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the high expression of c-fos occurs not only during sleep deprivation but also during spontaneous wake, indicating that its elevation is not due to the stress of sleep deprivation [31]. As a famous third messenger, the protein expressed by c-fos gene regulates the response of the body to external stimulation by activating or inhibiting its target genes [32], including inflammatory response. Zhang et al have reported that both c-fos and proinflammatory genes were promoted by high salt while the up-regulation of pro-inflammatory factors can be notably eliminated by the selective inhibitor of c-fos [33].…”
Section: Discussionmentioning
confidence: 99%
“…It has moreover been shown that some models of pathological conditions or therapeutic treatments act as strong neurogenic stimuli, which are able to activate stem cells also in adult mice, where "normal" neurogenic stimuli such as running are ineffective. These stimuli include electroconvulsive shock, which leads to massive cell depolarization (Segi-Nishida et al, 2008), traumatic brain injury (in the dentate gyrus, Gao et al, 2009, and in the early postnatal SVZ, Goodus et al, 2015), kainic acid (Hüttmann et al, 2003), and tetanus toxin (Jiruska et al, 2013) injections, which induce seizures, or also clozapine-N-oxide-mediated activation of the Gq protein in stem cells (Dong et al, 2019). Also focal ischemia typically induces an increase of neurogenesis in the dentate gyrus (Kee et al, 2001) as well as in the SVZ (Thored et al, 2006).…”
Section: High Intensity Activators Of Dentate Gyrus and Svz Stem Cellsmentioning
confidence: 99%